Upaya Guru PAI Dalam Mengatasi Kesulitan Belajar Baca Tulis Al-Quran - Nurseha, Afif; Saputra, Ajat (PT. Banjarese Pacific Indonesia, 2023)
The teacher's efforts in Islamic education are to educate, educating is a very broad task. Education is partly carried out in the form of teaching, partly in the form of encouraging, praising, punishing, giving examples, getting used to it, and so on. (Ahmad Tafsir, p.12 ). The obstacles that exist at the time of learning are many such as, the lack of learning hours for Islamic religious education in schools, the lack of discipline from students, environmental factors that cause them to be lazy to learn to read the Qur'an at an early age, and family factors that do not encourage their children to learn to read and write the Qur'an. The efforts of teachers are expected to be able to help overcome the problem of difficulty reading the Qur'an and make it their special purpose to overcome the difficulty of reading the Qur'an in MTs Manbatul Fikri Cururugrendeng. The teacher is an educator after the parents so the teacher has an important role in shaping the character. To find out the efforts of teachers to teach qur'an literacy, difficulty learning to read and write the qur'an, factors of difficulty reading and writing the qur'an, obstacles to the difficulty of reading and writing the Qur'an and the efforts of teachers in overcoming the difficulties of learning to read and write the Qur'an in MTs Manbatul Fikri Cururugrendeng, to find out the problems that exist in MTs Manbatul Fikri Cururugrendeng researchers use descriptive qualitative research methods by making observations, interviews, and documentation. Based on the results of research, the teacher's efforts in terms of educating and teaching about the literacy of the Qur'an to students when teaching are: The teacher conveys almost the same group of letters as Ta with Tsa, Sin with Syin, Dzal with Za. Then next is the grouping of children who have not been biased to read with those who are already fluent with the aim that those who are already fluent can guide those who are not yet fluent.